SIGNIFICANCE OF DIAGNOSTICS OF THE EPSTEIN-BARR VIRUS BY THE ELISA METHOD - Yodgorova N.T; Abdullayev U.M; Eshbekova L.SH (Scholar Express Journals, 2023)
Investigation of anti-EBV IgM va anti-EBV IgG against the Epstein-Barr virus by ELISA and antigen analysis. Material and methods: Materials of the InterMed private clinic located in the Yunusabad district of Tashkent in 2022 were used. For the study, 5 ml of blood from the wrist vein was taken from patients and examined by ELISA (BektoVEB-VCA-IgG-IGM, D2176, D-2184, Vector-Best JSC, Novosibirsk). The results obtained were subjected to statistical processing
Keywords: Epstein-Barr virus; Immunoenzyme analysis; mononucleosis; oncological diseases